Penerapan Pendekatan Kontekstual Dengan Strategi Numbered Heads Together Untuk Meningkatkan Motivasi Belajar Matematika Siswa Kelas IVA SDN Bentak 2 Tahun Ajaran 2015/2016 - Hariyanto, Adika (2016)
ABSTRACK Adika Hariyanto/A510120059 CONTEXTUAL APPROACH TO THE STRATEGY IMPLEMENTATION NUMBERED HEADS TOGETHER LEARNING MOTIVATION TO INCREASE CLASS IVA snapped SDN BENTAK 2 ACADEMIC YEAR 2015/2016. The Faculty of Education, University of Muhammadiyah Surakarta. January, 2016. Class Action Research aims to boost students' motivation to learn Maths class IVA s SDN Bentak 2 school year 2015/2016.through contextual approach with Numbered Heads Together strategy. This research is a classroom action research cycle model. The subjects of this study were students and teachers at SDN IVA snapped 2. The data collection using by observation, interview, and documentation to determine the level of student motivation SDN snapped IVA class 2 2015/2016 academic year before action and after the action. The data analysis techniques with step data reduction, data presentation and conclusion / verification. Based on the results of the action cycle 1 and cycle 2 showed that an increase motivation by 35% of students who are motivated either end of cycle 1 who initially before PTK only 20% to 55% and menigkat 25% diahkir cycle of 2 to 80% (16 students out of 20 students motivated either. In addition, an increase in the percentage of achievement indicators are: Indicator 1 increased from 40% before the PTK to 85% at the end of cycle 2, Indicator 2 meningakat from 45% before the PTK to 75% at the end of cycle 2, indicator 3 meningakat of 40% before PTK to 80% at the end of cycle 2, Indicator 4 meningakat from 30% before to 85% of PTK end of cycle 2, Indicator 5 meningakat from 35% before the PTK to 85% at the end of cycle 2. Thus, it can be suggested that the contextual approach to strategy Numbered Heads Together can increase students' motivation Keywords: Contextual Approach, Strategy Numbered Heads Together, Motivation